Effect of heavy cryo-rolling on the evolution of microstructure and texture during annealing of equiatomic CoCrFeMnNi high entropy alloy. (February 2016) - Sathiaraj, G. Dan; Bhattacharjee, P.P.; Tsai, Che-Wei; Yeh, Jien-Wei
Abstract: The effect of cryo-rolling on the evolution of microstructure and texture during annealing was investigated in equiatomic CoCrFeMnNi high entropy alloy. For this purpose the alloy was cold- and cryo-rolled to 90% reduction in thickness followed by annealing at temperatures ranging from 700 °C to 1200 °C. The two alloys showed the development of predominantly brass type deformation texture consistent with profuse nano-twin formation reported in this alloy. The cryo-rolled material showed significantly finer grain size after different annealing treatments as compared to the cold-rolled alloy. This could be attributed to finer microstructure in the cryo-rolled material providing greater number of available sites for nucleation. The recrystallization texture of cold- and cryo-rolled materials showed the presence of similar texture components indicating that cryo-rolling had limited effect on the formation of annealing texture. The volume fractions of different texture components did not reveal significant dependence on the annealing temperature. The evolution of texture could be explained on the basis of absence of strong preferential nucleation and growth during annealing. Highlights: Effect of cryo-rolling on annealing texture of HEA is reported. Recrystallized grain size is significantly smaller in cryo- than cold-rolled HEA. Evolution of annealing texture in cryo-rolled is similar to cold-rolled HEA. Absence of preferential nucleation or growth during annealing.